Obstacle Avoiding Berbasis Remote Control - Cornelia, Noni; Jaka Pratama, Dwi; Zandiyanto, Alex; Mahrijal, Mahrijal; Dwisaputra, Indra (LPPM Universitas Negeri Semarang, 2024)
Abstract— This project aims to develop a remote-controlled obstacle-avoiding system using the MIT App Inventor application. The system comprises several key components, including an Arduino Uno, an HC-05 Bluetooth module, and ultrasonic sensors. The Arduino Uno serves as the main microcontroller that manages all hardware components. The HC-05 Bluetooth module is used to establish a connection between the system and a mobile application developed with MIT App Inventor. Ultrasonic sensors are utilized to detect obstacles around the vehicle. In its implementation, the MIT App Inventor application is employed to remotely control the vehicle's movement direction via Bluetooth connectivity provided by the HC-05 module. Data from the ultrasonic sensors are processed by the Arduino Uno to measure the distance to obstacles and automatically adjust the vehicle's direction if an obstacle is detected too close. Test results demonstrate that the system can effectively detect and avoid obstacles and can be controlled efficiently through the mobile application. The use of MIT App Inventor allows for the creation of an intuitive and user-friendly interface without requiring complex programming. This system has the potential to be applied to various types of autonomous vehicles and robotics, offering an efficient and easily implementable solution for remote-controlled obstacle avoidance.